Anticancer Activity of Kefir on Glioblastoma Cancer Cell as a New Treatment - Arghavan Fatahi; Neda Soleimani; Parviz Afrough (International Journal of Food Science)
Kefir drink is one of the most important probiotic products, which is made using kefir microorganisms in fermenting the milk. Numerous investigation have been accomplished in the field of the therapeutic property of probiotic products. In the present study, we assessed the cytotoxic effect of kefir on the rate of growth and increase of glioblastoma cancer cell as the most severe form of brain tumors. In this experimental study, we used a U87 cancer cell line (glioblastoma). The interaction between cancer cells and different concentrations of kefir drink and supernatants at 24 and 48 hours was considered. The cell cytotoxicity of kefir and sedimentation of cell lysate and extract of kefir was assessed using the MTT test after 24 and 48 hours. The result of the MTT test, treatment of the cells with the 48-hour fermented drink, demonstrated the most cell cytotoxicity in comparison with the control group. Results showed that the toxicity effect in all groups was dose-dependent, and by increasing the concentration, cell survival decreased noticeably. The results indicated that the supernatant of fermented kefir drink as a probiotic product has more toxicity and lethality effect on the glioblastoma cancer cell. This product can be utilized as a replacement or a complementary therapy of cancer.